Selective oxidation of 5-hydroxymethylfurfural to 2, 5-furandicarboxylic acid over Au/CeO2 catalysts: the morphology effect of CeO2. Issue 7 (22nd March 2019) - Li, Qingqing; Wang, Haiyong; Tian, Zhipeng; Weng, Yujing; Wang, Chenguang; Ma, Jianru; Zhu, Chaofeng; Li, Wenzhi; Liu, Qiying; Ma, Longlong
Abstract : A morphological effect of Au/CeO2 catalysts in 5-hydroxymethylfurfural (HMF) oxidation. Abstract : 5-Hydroxymethylfurfural (HMF) which is derived from cellulosic biomass is an important platform for value added downstream chemicals and fuels via diversified processes. Nanoceria rods, cubes and octahedra were synthesized by a hydrothermal method and used as supports for preparing Au/CeO2 catalysts via deposition–precipitation. The morphology effect of CeO2 in the Au/CeO2 catalysts was investigated in selective oxidation of HMF to 2, 5-furandicarboxylic acid (FDCA). The Au/CeO2 -rod was more efficient for the oxidation of HMF and the TOF value of Au/CeO2 -rod was 6.3 (min −1 ), which was 7 times as high as that of Au/CeO2 -cube (0.9 min −1 ) and 32 times as high as that of Au/CeO2 -oct (0.2 min −1 ). The experimental results and catalyst characterization implied that the oxygen vacancies on the Au–CeO2 interface determined the catalytic activity by affecting the size, and valence of Au and the interfacial acidic properties. The Au/CeO2 -rod with the highest oxygen vacancies presented the higher proportion of cationic gold and more interfacial Lewis acidic sites between ceria and Au nanoparticles. Moreover, a synergistic effect between the interfacial Lewis acid, homogeneous base and neighboring Au particles promoted the oxidation reaction via efficiently activating the hydroxyl, aldehyde and molecular O2 .